(untitled) (Comprehensive Journal of Science, 2025)
Internal combustion engine oils play a significant and vital role in engine service life and extending its lifespan. The purpose of this study was to examine the effect of mileage on the physical and chemical properties of a sample of diesel engine oils available in the Libyan market. In this study, several laboratory experiments were conducted at the Libyan Oil Research Center and the Zawiya Oil and Gas Refinery on a sample of Italian-made IVECO Urania SAW 15W-40 diesel engine oil after using it for varying distances (0 km, 3,500 km, 5,000 km, and 10,000 km). In addition to measuring viscosity, which is considered one of the most important and reliable parameters for assessing the properties and lifespan of the used oil, this research also examined other equally important properties, namely density, pour point, flash point, and ash percentage. A used oil sample was taken from a four-cylinder diesel engine with an age of 120,000 km, belonging to a (Iveco Cursor ) model. The results of this study showed that the effect of distance traveled on the studied properties was clear and noticeable. For example, the viscosity decrease reached 15.43% at 40°C and 11.7% at 100°C for a distance of 5,000 km compared to a distance of 0 km, and an increase in the average density by 0.114%. The rate of change in flash point was also clear from 226°C at 0 km to 228°C at 5,000 km. The ash content of the used oil increased by 13.27% compared to a distance of 0 km, and the pour point was less than -30°C.